2011
DOI: 10.1101/gr.125591.111
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of matched primary and metastatic acral melanomas

Abstract: Next generation sequencing has enabled systematic discovery of mutational spectra in cancer samples. Here, we used whole genome sequencing to characterize somatic mutations and structural variation in a primary acral melanoma and its lymph node metastasis. Our data show that the somatic mutational rates in this acral melanoma sample pair were more comparable to the rates reported in cancer genomes not associated with mutagenic exposure than in the genome of a melanoma cell line or the transcriptome of melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
148
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(161 citation statements)
references
References 64 publications
12
148
1
Order By: Relevance
“…Examining of human cadaveric nails has previously showed that all of UVB and the vast majority of UVA light is blocked by the nail plate. 14 The fact that two of the cases we reported in the thumb and a previous case report in the toe 28 of subungual melanoma with a dominant UVR signature appears to refute these findings. It would therefore appear that in some patients sufficient UVR can penetrate the nail plate to cause mutation effects in the melanocytes in the underlying subungual tissue.…”
Section: Acral and Subungual Melanomas With A Dominant Uvr Signaturementioning
confidence: 53%
See 2 more Smart Citations
“…Examining of human cadaveric nails has previously showed that all of UVB and the vast majority of UVA light is blocked by the nail plate. 14 The fact that two of the cases we reported in the thumb and a previous case report in the toe 28 of subungual melanoma with a dominant UVR signature appears to refute these findings. It would therefore appear that in some patients sufficient UVR can penetrate the nail plate to cause mutation effects in the melanocytes in the underlying subungual tissue.…”
Section: Acral and Subungual Melanomas With A Dominant Uvr Signaturementioning
confidence: 53%
“…In previous exome and whole-genome sequencing studies, mutations per Mb in acral melanomas have been reported to range from 1.02 to 3.68 (5 cases), 15 1.95, 28 and 2.79 to 14 (two cases). 27 In contrast, the mean mutation rate of The Cancer Genome Atlas Network study, 20 which consisted entirely of cutaneous melanomas, was 16.8 mutations/Mb.…”
Section: Acral and Subungual Melanomas With A Dominant Uvr Signaturementioning
confidence: 98%
See 1 more Smart Citation
“…Melanoma, like other cancers, arises and evolves through the accumulation of genetic alterations within tumor cells (7)(8)(9). Comparing somatic mutations in primary tumor and regional and distant metastases from the same patient can provide insight into the phylogenetic relationships between these distinct tumor cell populations and the order of metastatic dissemination (8,10).…”
mentioning
confidence: 99%
“…Comparing somatic mutations in primary tumor and regional and distant metastases from the same patient can provide insight into the phylogenetic relationships between these distinct tumor cell populations and the order of metastatic dissemination (8,10). These analyses may also establish whether cells in the primary tumor that metastasize acquired this ability to disseminate and seed other anatomic sites by a newly acquired genetic alteration, or whether metastatic colonization is simply a stochastic process of which all cells in the primary are capable but few succeed.…”
mentioning
confidence: 99%